Nursing Care for Low-Birth Weight Babies With Hypothermia Using Kangaroo Mother Care: A Case Study - Ni Wayan Juni Winata Sari; Putu Indah Sintya Dewi; Ni Putu Diah Ayu Rusmeni (STIKes Budi Luhur Cimahi, 2025)
Low-birth weight (LBW) infants are at risk of hypothermia due to immature thermoregulatory mechanisms. LBW is defined as a birth weight of less than 2,500 grams regardless of gestational age. Hypothermia can occur in LBW infants even in relatively warm environments, as newborns are unable to regulate their body temperature optimally. If not treated promptly, hypothermia may lead to serious illness or even death. To increase body temperature in LBW infants, an alternative therapy such as Kangaroo Mother Care (KMC) can be applied. This study aims to describe nursing care for LBW infants experiencing hypothermia using Kangaroo Mother Care therapy. A descriptive case study design was employed to identify nursing problems. The subject of this study was Baby J. The nursing diagnosis established was hypothermia. Nursing interventions focused on managing hypothermia through KMC therapy, which was administered twice daily for one hour over a period of three consecutive days. Prior to the intervention, an assessment was conducted to identify signs of hypothermia, such as body temperature, lip color, and the infant's general condition. During therapy, Baby J’s mother received direct guidance due to limited knowledge about the correct application of KMC. This required time and educational support from healthcare professionals. After 72 hours of intervention, evaluation results showed an increase in the infant’s body temperature to within the normal range, warm skin, and improved breastfeeding activity. These findings indicate a reduction in hypothermia symptoms. The study concludes that KMC is beneficial in supporting thermoregulation in LBW infants. Kangaroo Mother Care therapy has proven effective in increasing body temperature in LBW patients.